Sistem Pendukung Keputusan Pemilihan Mobil Menggunakan Metode WASPAS - Rakadhea Dimaski; Jati Sasongko Wibowo (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
The more diverse choices of cars offered, making consumers often confused to make a choice whether from the brand, model, type, price, engine capacity, transmission, year of manufacture and fuel capacity as well as the advantages of the car. The car selection process still uses a manual system, namely by using conventional brochures or catalog media and usually consumers make purchases only because they are interested in the latest model or appearance and facilities without being adjusted to their needs. This study aims to create a system that can be used in the selection of cars according to consumer desires and apply the WASPAS method in providing recommendations for car selection based on the criteria of brand, model, type, price, engine capacity, transmission, year of manufacture and fuel capacity. The results of the recommendations from the selection of criteria for the Honda brand and CVT transmission resulted in a recommendation for the Honda Brio. Honda Brio has the highest value because it has the lowest price where the price criterion has the highest percentage of weight